The complete chloroplast genome sequence of Durio oxleyanus (Malvaceae) and its phylogenetic position - Wong, Xue Jing; Law, Douglas; Zheng, Feng Wang; Ramaiya, Shiamala Devi; Lee, Shiou Yih (Taylor and Francis, 2022)
Durio oxleyanus (Griff) of Malvaceae is considered a natural heritage by the countries that produce it, including Peninsular Malaysia, Sumatra, and Borneo. Even though the species is regarded as a commercially valuable fruit, cultivation of this species is uncommon. The dwindling population of this species in the wild has put its survival in jeopardy. Conservation efforts are required for this species, which are limited. In this study, the complete chloroplast (cp) genome of D. oxleyanus was assembled and characterized as a genomic resource for conservation programs. The complete cp genome size was 164,831 bp in length, with a pair of inverted repeats of 23,782 bp each, separating the 96,446-bp large and the 20,823-bp small single copies. A total of 135 genes were predicted, which consisted of 90 protein-coding, 37 tRNA, and eight rRNA genes. The overall GC content was 35.8%. The phylogenetic analysis based on the maximum-likelihood and Bayesian inference methods revealed that D. oxleyanus is closely related to D. zibethinus. The genomic data obtained will be useful for future studies of Malvaceae's phylogenetics and evolution.